Challenges of wealth-based sustainability metrics: A critical appraisal - Eoin McLaughlin; Cristián Ducoing; Nick Hanley (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
There has been widespread debate about whether the way in which we measure economic activity is fit for purpose in the twenty-first century. One aspect of this debate is to move away from measuring a nation's income (GDP) towards monitoring a nation's assets (their inclusive wealth), as a better indicator of sustainable economic development. We provide the first critical comparison of the approaches of leading international organisations - the World Bank and the United Nations Environment Programme - to estimating changes in wealth. Our paper reveals important inconsistencies in how these organisations measure sustainability and the conflicting messages that policy makers receive, despite a common underlying conceptual framework linking changes in a nation's wealth to future well-being. At the most extreme, countries that perform the worst according to the UN are shown to perform well according to the World Bank. This confusion in signals makes better policy making more difficult.
Keywords: Q01; Q32; Q56; N50; N10; O13; O44; 330; Wealth; Sustainability; Natural Capital; Sustainable Development